BERKELEY'S IDEALISM AND AMAZONIAN ISSUES - Barbosa, Cloves; Wilson Tafner Junior, Armando (Revista Gênero e Interdisciplinaridade, 2026)
This paper introduce the Berkeley’ idealism and his place into the philosophical theory. the Anglo-Saxon Church’ bishop made your theory about church-yard focus and has the goals against the atheisms conceptions. The Berkeley philosophical idealism was made with this first propos.